Analgesic Effects of Sevoflurane and Isoflurane on Elderly Patients with Colon Cancer and Their Influences on Immunity and Postoperative Cognitive Function - Mingde YANG; Yan YU; Quanfeng LIU (Tehran University of Medical Sciences, 2019)
Background: We aimed to investigate the analgesic effect and immune function of elderly patients with colon cancer after application of sevoflurane and isoflurane anesthesia. Methods: Overall, 130 patients with colon cancer in Yidu Central Hospital of Weifang  (Weifang, China) from February 2014 to January 2017 were collected and randomly divided into sevoflurane group (SEV group) and isoflurane group (ISO group). The pain score, immune indexes, postoperative cognitive index, extubation time, awakening time and S100R protein were analyzed. Results: The pain scores in SEV group at 5 min, 1 h and 3 h during surgery were significantly lower than those in ISO group (P=0.001, respectively). The levels of IL-6 in both groups of patients were higher at T1 and T2 than those at T0 (P=0.001). The levels of TNF-α in SEV group at T2 and T3 were significantly higher than that at T0 (P=0.001). The levels of CD80 in both groups of patients at T2 and T3 were obviously higher than those at T0 (P=0.001). Moreover, the extubation time, the response time to language and awakening time in SEV group were also remarkably shorter than those in ISO group (P=0.001). After continuous anesthesia in both groups of patients, the degrees of decline in ISO group were significantly higher than those in SEV group (P=0.001). Conclusion: Sevoflurane has a superior anesthetic effect to isoflurane in elderly patients with colon cancer, can reduce the degree of pain, improve the awakening condition and increase the immune function, so it is worthy of clinical application.